Integration of NMR and NMRC in the Investigation of the Pore Size Distribution of Tight Sandstone Reservoirs: A Case Study in the Upper Paleozoic of Dongpu Depression - Ning Zhu; Suping Yao; Xuejun Wang; Binfeng Xia; Yunxian Zhang (Geofluids)
Exploring appropriate methods to understanding the pore structure and overall pore size distribution (PSD) of tight sandstone reservoir is important for evaluating the quality of the reservoir. An integration analysis comprising X-ray diffraction (XRD), three beams of argon ion (TIB) polishing approach, scanning electron microscopy (SEM), high-pressure mercury intrusion (HPMI), nuclear magnetic resonance (NMR), and nuclear magnetic resonance cryoporometry (NMRC) was applied to determine the pore structure of the tight sandstone reservoirs in the Upper Paleozoic of Dongpu Depression as well as their relationship with the physical properties of the reservoirs. NMRC offered the possibility to obtain the nanoscale (4-1400 nm) pore structure of the reservoirs directly and accurately. Therefore, an attempt by combining NMRC and NMR can reveal the PSD of tight sandstone reservoirs with different pore structures. The results showed that the tight sandstone reservoirs consisted of intergranular, intragranular, and intercrystalline (clay mineral) pores. The full PSD intelligibly showed pore structure characteristics of four different types of reservoirs, with pore sizes ranging from 2 nm to dozens of microns. Specifically, the overall PSD of type I reservoirs showed a broad unimodal distribution pattern with the peaks in the range 0.1–2 μm, indicating an association with dissolution intergranular pores, and for type II reservoirs, the overall PSD showed a bimodal distribution pattern, with their left and right peaks, in the ranges 0.004–0.01 μm and 0.15–0.4 μm, respectively, showing similar amplitudes, implying the predominance of both intergranular (mesopores) and intergranular (macropores) pores. The full PSDs of type III and IV reservoirs showed much lower amplitudes than type I and II reservoirs, indicating a lower pore number and a complex pore structure. Furthermore, NMRC also demonstrated that different diagenesis resulted in a correlation between pore structure and reservoir physical properties.